Influence Of Human Capital Management And Work Discipline On Employee Performance at PT. Bumi Mineral Sulawesi - Saskia, Saskia; Haedar, Haedar; Indra, Indra (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose:This study aims to analyze the effect of Human Capital Management (HCM) and work discipline on employee performance at PT Bumi Mineral Sulawesi. Methodology: The research employs a quantitative approach with a saturated sampling technique involving all 72 employees as respondents. Data were collected through observations and structured questionnaires using a Likert scale. The data were analyzed using multiple linear regression supported by validity and reliability tests.Results: The findings reveal that Human Capital Management does not have a significant effect on employee performance. In contrast, work discipline has a positive and significant effect on employee performance. Simultaneously, HCM and work discipline significantly influence employee performance. Novelty: This study highlights the dominance of work discipline over Human Capital Management in influencing performance within the nickel processing industry.Findings: Work discipline emerges as the most influential factor in improving employee performance, while HCM requires better alignment with operational needs. Originality: The originality of this study lies in its empirical evidence from a nickel processing company in Indonesia, a sector rarely examined in HCM research. Conclusions: Strengthening work discipline and optimizing the implementation of Human Capital Management are essential to improving employee performance. Type of Paper: Empirical Research Paper.